Assessing the Reliability of a Small-Scale Legacy Radiocarbon Dataset Using Chronometric Transparency Approaches: Torres Strait Radiocarbon Database. (16th February 2023) - Linnenlucke, Lauren; I. Bird, Michael; Petchey, Fiona; Alliston, Geordie; J. McNiven, Ian; David, Bruno; Ulm, Sean
A new quality assurance framework was developed to assess the reliability of 14 C ages from a small-scale legacy dataset from archaeological sites across the Torres Strait (northeastern Australia). Chronometric transparency principles were applied across three stages of data analysis, comprising of a basic, immediate, and advanced assessment of the 14 C ages and associated metadata. Reliability ratings (1*, 2*, 3*, and 4*) were assigned to represent data confidence in individual radiocarbon ages. Results demonstrate the utility of radiocarbon ages of high, medium, and low reliability in creating chronological reconstructions. We determine that of the 343 14 C ages, 73% were awarded a reliability rating of 3* or above.